The Dynamic Effect of Social and Political Instability on Output : The Role of Reforms - Bernal-Verdugo, Lorenzo E.; Furceri, Davide; Guillaume, Dominique (Washington, D.C. : International Monetary Fund, 2013)
The aim of this paper is to analyze the dynamic effect of social and political instability on output. Using a panel of up to 183 countries from 1980 to 2010, the results of the paper suggest that social conflicts have a significant and negative impact on output in the short-term with the magnitude of the effect being a function of the intensity of political instability. The results also show that the recovery of output over the medium-term depends on the ability of the country to implement, in the aftermath of a social instability episode, reforms aimed at improving the level of governance. The results are robust to different checks and estimation strategies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Crisis, Growth; Governance Indicator; Reforms; Social Conflicts; WP; Egypt, Arab Republic of